Analysis Of Human Resource Competency, Internal Control System, Quality Of Financial Statements and Application Of Government Accounting Standards To Accountability Of Performance Of Government Agencies In Pegunungan Bintang Regency - Ramasoyan Ramasoyan; Pascalina Van Sweet Sesa; Kurniawan Patma; Rudiawie Larasati (Journal of Social Science, 2021)
Regional device organization (OPD) of Pegunungan Bintang Regency. The internal control system has a significant effect on the accountability of the performance of government agencies in the Purpose Organization in this study to know and analyze the influence of human resource competence, the influence of internal control systems influence the quality of financial statements, the implementation of government accounting standards on government performance accountability,and silmultan to the accountability of government agencies performance. The population in this study is employees of the Regional Device Organization (OPD) Of Pegunungan Bintang District who routinely carry out inspection tasks and have a minimum educational background diploma 3 (D3) Accounting, have attended JFA training (Auditor Functional Department) and have a minimum work experience of 1 Year. The analysis techniques used are multiple regression analysis techniques to process and discuss the data that has been obtained and test the proposed hypothesis. The results of the analysis are known that human resources competency variables have a significant influence on the accountability of the performance of government agencies Regional Devices (OPD) Gunung Bintang District,the quality of financial statements have a significant effect on the accountability of the performance of government agencies in the Regional Device Organization (OPD) Gunung Bintang District.